Bacteroides fragilis aortic arch pseudoaneurysm: case report with review - Yang Yu-Jen; Liu Kung-Hung; Lee Hsin-Ling; Kan Chung-Dann (Journal of Cardiothoracic Surgery, 2008)
Abstract We present a case of 58-year-old woman with underlying diabetes mellitus, hepatitis C virus-related liver cirrhosis, and total hysterectomy for uterine myoma 11 moths ago, who was diagnosed ruptured aortic arch mycotic pseudoaneurysm after a certain period of survey for her unknown fever cause. After emergent surgery with prosthetic graft interposition, all her blood cultures and tissue cultures revealed pathogen with Bacteroides fragilis. Although mycotic aneurysms have been well described in literatures, an aneurysm infected solely with Bacteroides fragilis is unusual, with only eight similar cases in the literature. Here we reported the only female case with her specific clinical and management course and summarized all reported cases of mycotic aneurysm caused by Bacteroides fragilis to clarify their conditions and treatments, alert the difficulty in diagnosis, and importance of highly suspicious.